2007
DOI: 10.1111/j.1547-5069.2007.00176.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Caregiver Mastery on Depressive Symptoms

Abstract: Findings showed a link between care recipients' problem behaviors and caregivers' depressive symptoms, a relationship that has not been well established in oncology. This association indicates one mechanism through which problem behaviors in the care recipient might lead to caregiver depressive symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(70 citation statements)
references
References 33 publications
2
66
1
Order By: Relevance
“…Finally, the extent of caregiving was the only background variable that had a direct positive effect on depression, as confirmed among other populations as well (Matsuu et al, 2000;Yates et al, 1999). Our results showed that sense of mastery was the major (negative) predictor of depression among ArabIsraeli caregivers, as has been reported among other populations (Clair et al, 1995;Pioli, 2010;Rozario & DeRienzis, 2008;Sherwood et al, 2007;Yates et al, 1999). This finding suggests that psychological resources, such as the sense of mastery, appear to protect even traditional caregivers from negative mental health consequences.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Finally, the extent of caregiving was the only background variable that had a direct positive effect on depression, as confirmed among other populations as well (Matsuu et al, 2000;Yates et al, 1999). Our results showed that sense of mastery was the major (negative) predictor of depression among ArabIsraeli caregivers, as has been reported among other populations (Clair et al, 1995;Pioli, 2010;Rozario & DeRienzis, 2008;Sherwood et al, 2007;Yates et al, 1999). This finding suggests that psychological resources, such as the sense of mastery, appear to protect even traditional caregivers from negative mental health consequences.…”
Section: Discussionsupporting
confidence: 75%
“…Particular attention has been given to the sense of mastery as a factor that may prevent caregivers from becoming increasingly stressed over time (Clair et al, 1995;Pearlin & Schooler, 1978;Pioli, 2010;Rose, Mallinson, & Gerson, 2006;Sherwood et al, 2007;Yates, Tennstedt, & Chang, 1999). Studies cite a negative association between mastery and subjective caregiver burden (Clair et al, 1995;Miller, Cambpell, Farran, Kaufman, & Davis, 1995;Schreiner & Morimoto, 2003), as well as between mastery and caregiver depressive symptoms (Clair et al, 1995;Pioli, 2010;Rozario & DeRienzis, 2008;Sherwood et al, 2007;Yates et al, 1999).…”
Section: Introductionmentioning
confidence: 96%
“…Preparedness for Caregiving 14 and the Caregiving Mastery and Self-Competence scale 16 (Global Caregiver Self-Confidence and Self-Competence subscales) measure domains conceptually related to caregiver activation, and the Revised Scale of Caregiving Self-Efficacy 15 that captures caregivers' sense of control over specific caregiving and life tasks and the personal consequences of taking on a caregiving role.…”
Section: Concurrent Validitymentioning
confidence: 99%
“…Preparedness for caregiving14 A measure of caregivers' perception of how well prepared they are for various domains of caregiving (physical care, emotional support, dealing with caregiving stress).Revised scale of caregiving self-efficacy15 A measure of caregivers' perception of their ability to provide care for a care recipient and themselves (obtain respite, respond to difficult behaviors, control upsetting thoughts about caregiving).Caregiving mastery and self-competence16 A measure of dementia caregivers' sense of efficacy and personal control over their lives (relationships, finances, loss), and overall feeling of competence and confidence in a caregiving role.…”
mentioning
confidence: 99%
“…This suggests higher load of caregiving demands was related to lower satisfaction or gain. In another study with 95 caregivers of people with primary malignant brain tumor, Sherwood et al (2007) found that care recipients' problem behaviors predicted caregiver mastery as measured by the adapted personal mastery of Pearlin and Schooler (1978); higher numbers of problem behaviors related to lower caregiver mastery.…”
Section: Caregiving Satisfactionmentioning
confidence: 99%